NoSQL and SQL logical and physical data modeling with COMN - Hills, Ted; Safari eBooks ([Place of publication not identified] : Technics Publications, 2017)
"The Concept and Object Modeling Notation (COMN) supports contextual, logical, and physical data modeling for NoSQL and SQL DBMSs. In this advanced class, Ted Hills will walk through two physical models for a hypothetical coffee shop business, exploring a design for a document database for order capture and a traditional SQL database for data warehousing (a Star Schema). A COMN logical model ties it all together, ensuring that the two very different physical database designs are representing the same logical data. Along the way, Ted will explain the COMN notation."--Resource description page.
Title from resource description page (viewed December 15, 2017).
Presenter, Ted Hills.
Keywords: Distributed databases; Relational databases; Non-relational databases; SQL (Computer program language); Electronic books